Cortical Neuron Migration and Dendrite Morphology are Regulated by Carboxypeptidase E - Liang, Chen (Cereb Cortex, 2019)
Higher brain function relies on proper development of the cerebral cortex, including correct positioning of neurons and dendrite morphology. Disruptions in these processes may result in various neurocognitive disorders. Mutations in the CPE gene, which encodes carboxypeptidase E (CPE), have been linked to depression and intellectual disability. However, it remains unclear whether CPE is involved in early brain development and in turn contributes to the pathophysiology of neurocognitive disorders. Here, we investigate the effects of CPE knockdown on early brain development and explore the functional significance of the interaction between CPE and its binding partner p150(Glued). We demonstrate that CPE is required for cortical neuron migration and dendrite arborization. Furthermore, we show that expression of CPE-C10 redistributes p150(Glued) from the centrosome and that disruption of CPE interaction with p150(Glued) leads to abnormal neuronal migration and dendrite morphology, suggesting that a complex between CPE and p150(Glued) is necessary for proper neurodevelopment.